The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c7cp01008g
|View full text |Cite|
|
Sign up to set email alerts
|

Formic acid catalyzed isomerization of protonated cytosine: a lower barrier reaction for tautomer production of potential biological importance

Abstract: Tautomerism in nucleotide bases is one of the possible mechanisms of DNA mutation. In spite of numerous studies on the structure and energy of protonated cytosine tautomers, little information is available on the process of their intra- and intermolecular tautomerizations. The catalytic ability of HO, HCOOH, and the HCOOHHO group to facilitate the tautomerism of the Cyt2t to CytN3 isomer has been studied. It is shown that the activation free energies of tautomerism in the gas phase are 161.17, 58.96, 26.06, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Based on the previous work, the activation free energy of direct hydrogen transfer is obviously reduced by the contribution of a single water molecule. Then, the H 2 O‐mediated mechanism has been investigated.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Based on the previous work, the activation free energy of direct hydrogen transfer is obviously reduced by the contribution of a single water molecule. Then, the H 2 O‐mediated mechanism has been investigated.…”
Section: Resultsmentioning
confidence: 91%
“…The recent theoretical researches and our previous work indicate that the activation energy is likely to be further lowered in the presence of formic acid (HCOOH). Then, the ∆ G ≠ of direct tautomerization of KA to KIt isomer may be further affected by the contribution of the formic acid molecule.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As outlined in a previous work, [ 22–25 ] HCOOH acted as both donor and acceptor groups to imitate the interacting group of amino acid residues is of considerable interest in the intermolecular proton transfer from the hydroxo‐amino tautomer into the oxo‐amino one. Brovarets′ et al [ 26 ] have imitated the acetic acid involved in diproton transfer between canonical and mutagenic tautomers of DNA bases by the theoretical study.…”
Section: Introductionmentioning
confidence: 99%
“…The formic acid has recently been demonstrated that it could reduce the barriers for unimolecular isomerization involving hydrogen atom transfer in modeling biological molecules. [ 22–25 ] Taken HCOOH as a typical catalyst, the isomerization of other protonated isomers for new DNA bases into another canonical one is one of the great concerns.…”
Section: Introductionmentioning
confidence: 99%